Peran Kepala Sekolah Dalam Peningkatkan Mutu Sekolah Dasar Terintegrasi Qur’an Al-Wafi Depok - Viedy Dimas Aditya; Syamsudin Syamsudin; Abdul Hamid Bashori (STAI Publisistik Thawalib Jakarta, 2023)
The research objective was to identify and describe the role of the principal in improving the quality of Al-Wafi Qur'an Integrated Elementary School, Depok. Research using qualitative with a case study approach. Data collection techniques with interviews, documentation, and observation. Data analysis techniques with reduction, data presentation, and conclusion. Data validation techniques with transferability and dependability. The results of the study show: (1) The principal as an educator by fostering and guiding teachers and education. (2) The principal as a manager by managing the school. (3) The school principal acts as an administrator by managing school files. (4) The school principal acts as a supervisor with class, performance, and extracurricular supervision. (5) The principal as a leader by socializing the vision, and mission and creating a school climate (7) The principal as an entrepreneur by instilling an entrepreneurial spirit and marketing the school's flagship program.